GETDOC: DEVELOPMENT OF MEDICAL APPOINTMENT APPLICATION - Baharudin, Nur Nadirah Natasya (IRC, 2019)
Individuals are involved with numerous activities that are planned, unplanned, routine and emergency in nature. The ability to deal with all these activities without conflict is wanted by all people since time management is one of the qualities of fruitful people. The current standard working system in healthcare environment for patient registration and appointment booking are tedious and somehow tiresome and time consuming. Regularly we see patients going to clinic and filing out registration documents and waiting by to be called for getting appointment and wait for the responses for a concurred date. In certain places, appointment can be done via web online but yet, patient still need to walk in with the appointment card to be swiped by the front desk admin before being sent to meet the doctor. With the rapid increase of mobile devices in our society, this study was to develop an appointment application for mobile devices using the android platform. GetDoc Medical Appointment Application is a mobile application create for managing appointment-booking process for Clinic Dr Asmah regardless of the type of services the clinic offered. The user will have to sign up on the application portal themselves and can view the appointment made by them. The application will allow the patients to receive notifications on their medical appointment. By building up this application, it will reduce the number of calls for appointments at the clinic. Likewise, it will potentially diminish the need of extra reception staff at the clinic. Furthermore, this application will help user in time saving and avoiding the need to negotiate with the receptionist for a convenient appointment time. This application can change the current daunting appointment process and enable them to run more efficiently.